Improving The Quality Of Maternal Health Using The Assistance Method One Cadre One Mother - Anik Kurniawati; Rohmi Handayani (Poltekkes Kemenkes Surakarta, 2022)
Background: The efforts to accelerate the success of reducing the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) in addition to access and service factors, cross-sector participation, especially those related to maternal health efforts, is to increase cross-sectorquasi-experimental outlined in an activity assisting high-risk pregnant women by health cadres.Methods: This is a quantitative study using a quasi-experimental research design with a post-test and control group. The sample consisted of 20 third-trimester pregnant women in the treatment group who received cadre assistance until the postpartum period and 20 respondents in the control group, namely pregnant women who were not accompanied by cadres. The sample was selected using random sampling. Bivariate data analysis for each sub-variable used the independent T-test, Fisher extract, and chi-square. Results: Show that assisting health personnel has an effect on pregnant women's readiness for childbirth (p-value = 0.017) with a CI of (-7.07768–.72232). There is a link between assisting health care providers and breastfeeding practice in pregnant women (p-value = 0.002). There is no influence between assisting health cadres with postpartum health (p-value=0.487). Conclusion: With health professionals and their readiness for childbirth and breastfeeding practice. There is no influence between mentoring health cadres and postpartum health.